Grassroots Representation or Pro Forma Exercise? Cooperation and Participation in the Revitalization of Polish Municipalities - Przywojska, Justyna; Podgórniak-Krzykacz, Aldona (Journal of Regional and City Planning, 2025)
This article explores a participatory approach to revitalizing degraded urban areas. The study examined whether revitalization committees in Poland serve as platforms for cooperation among various stakeholders and to assess local authorities’ views on the importance of individual stakeholders in the revitalization process. This article presents the concept of sustainable revitalization as a response to urban crises and discusses the dilemmas and challenges associated with the participatory approach to planning and implementation. To gather opinions from local authorities on the functioning of revitalization committees and other advisory bodies that include revitalization stakeholders, quantitative research was conducted in 573 Polish municipalities. The online survey questionnaire was addressed to mayors or heads of villages and their deputies. The research results indicate that the permanent involvement of stakeholders in revitalization is not common among Polish municipalities. Although local leaders highly rated the importance of partnerships and local cooperation in revitalization and reported no difficulties in establishing revitalization committees, these committees operated in only 27% of the surveyed municipalities. The established revitalization committees are characterized by both administrative and social functions, predominantly comprising local government officials, local authorities, and NGO representatives. Business communities, vulnerable groups, and institutions addressing socio-economic issues in the revitalized areas are relatively underrepresented in these committees. A key finding of the study is the mismatch between the high importance assigned by local leaders to certain stakeholder groups and the limited presence of these groups in the composition of revitalization committees.